Study on RF module in UHF OFDM node for mobile multimedia sensor network - PANG Rui-fan; JIANG Jian; WANG Ying-guan; ZHANG Hong-jun; LIU Hai-tao (Tongxin xuebao, 2008)
A design of radio frequency （RF） module in ultra high frequency （UHF） orthogonal frequency division multi-plexing （OFDM） node for mobile multimedia sensor network was presented. It adopts direct frequency conversion and power back-off technologies, supports high speed multiplex data transmission in time division multiple access （TDMA） mobile network, and has the ability of high linearity, high sensitivity, wide dynamic range and high out-of-band suppres-sion. It can be applied to very important person （VIP） motorcade video wireless monitoring system, public security emergency command system, and battlefield surveillance system, etc.